Penerapan Sistem Informasi Akuntansi Persediaan Dalam Pengambilan Keputusan Pembelian Pada CV Lufitech Indonesia - Nurjanah, Yayuk; P, Robert Pius; Andrian, Andrian (Jurnal Ilmiah Akuntansi Kesatuan, 2015)
The purpose of this study is to determine that the application of inventopy accounting information systems can assist in supporting the operations management and decision-making on purchase of the CV Lufitech Indonesia. The study authors used the data card Stock is the raw material inventory in CV Lufitech Indonesia in Januan.' and ending in February 2014. The analytical method used is descriptive qualitative authors, by analyzing the data obtained from the questions and the data provided by the company through observation and interviews. The results of the study on CV Lufitech Indonesia concluded that the inventory accounting information systems are Still manual recording, do not have a specific system in inputting inventory on the company, leading to a purchase decision is not necessarily. Application of inventory accounting system is Still very minimal and voy influential ifapplied to support the purchase order control. Keywords: Inventory Accounting Information Systems, Purchasing Decisions